Extracellular hemoglobin: the case of a friend turned foe - Quaye, Isaac K. (Frontiers in Physiology, 2015)
Hemoglobin (Hb) is a highly conserved molecule present in all life forms and functionally tied to the complexity of aerobic organisms on earth in utilizing oxygen from the atmosphere and delivering to cells and tissues. This primary function sustains the energy requirements of cells and maintains cellular homeostasis. Decades of intensive research has presented a paradigm shift that shows how the molecule also functions to facilitate smooth oxygen delivery through the cardiovascular system for cellular bioenergetic homeostasis and signaling for cell function and defense. These roles are particularly highlighted in the binding of Hb to gaseous molecules carbon dioxide (CO2), nitric oxide (NO) and carbon monoxide (CO), while also serving indirectly or directly as sources of these signaling molecules. The functional activities impacted by Hb outside of bioenergetics homeostasis, include fertilization, signaling functions, modulation of inflammatory responses for defense and cell viability. These activities are efficiently executed while Hb is sequestered safely within the confines of the red blood cell (rbc). Outside of rbc confines, Hb disaggregates and becomes a danger molecule to cell survival. In these perpectives, Hb function is broadly dichotomous, either a friend in its natural environment providing and facilitating the means for cell function or foe when dislocated from its habitat under stress or pathological condition disrupting cell function. The review presents insights into how this dichotomy in function manifests.